Rancang Bangun Sistem Informasi Penggajian Pegawai Berbasis Web di Madrasah Ibtidaiyah Nurul Huda Kota Tangerang - Rohmat Taufiq; Risma Rohmatul Ummah; Irfan Nasrullah; Angga Aditya Permana (Teknik Informatika Universitas Pamulang, 2019)
Madrasah Ibtidaiyah Nurul Huda Kota Tangerang is one of the private schools, but data processing payroll in this schooll was still unintegrated. The ongoing payroll system was still in use of a manual system. The results of this were many obstacles faced by the school in the production of materials such as in payroll contracts, payroll calculations, payroll slips, and drawing up payroll reports. Also, the information presentation was less fast, inexact, inaccurate because current media transmission information consists of purely physical documents. The research method used waterfall method. Waterfall is a model of its development process for the coverage of a system, sequential or linear. The research steps were divided into: analysis, design, coding, testing and maintenance. The system would then be built using synthetic programming language PHP and Mysql as a database. The web-based employee payroll information system was intended to provide advantages in payroll data processing such as payroll process, payroll calculations, payroll slips, and payroll reports, so that manual jobs could be much easier and computerized. The result was derived from this research was development of the web-based employee payroll information system.